Gente Kayapo - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó a una mamá del grupo etnico Kayapo pintando con colores naturalez provenientes de vegetales de color negro a su pequeño hijo conocido con el nombre de "Cenipapo" cuya mescla es con polvo de carbon molido con una duracion aproximado de 10 dias.
ENGLISH: A mother from the Kayapo ethnic group was observed painting her little son known by the name of "Cenipapo" with natural colors from black vegetables, whose mixture is with ground charcoal powder with a duration of approximately 10 days.

SPANISH: Se observó a una mamá del grupo etnico Kayapo pintando con colores naturalez provenientes de vegetales de color negro a su pequeño hijo conocido con el nombre de "Cenipapo" cuya mescla es con polvo de carbon molido con una duracion aproximado de 10 dias.
ENGLISH: A mother from the Kayapo ethnic group was observed painting her little son known by the name of "Cenipapo" with natural colors from black vegetables, whose mixture is with ground charcoal powder with a duration of approximately 10 days.
Kayapo People
Keywords: Mato Grosso (Brasil)--Indigenous Community|~|Brazil--Indigenous populations|~|Mato Grosso (Brasil)|~|Comunidad Indigena|~|Brasil|~|Poblaciones Indigenas|~|Mato Grosso (Brazil)|~|Indigenous Community|~|Brazil|~|Indigenous Populations